2022
DOI: 10.3390/ma15196882
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Defects on the Fatigue Behavior of Additive Manufactured Metal Components: A Comparison between Ti6Al4V and Inconel 718

Abstract: In order to obtain a widespread application of Additive Manufactured (AM) technology in the aircraft industry for fatigue critical parts, a detailed characterization of the Fatigue and Damage Tolerance (F&DT) behavior of structural components is required. Metal AM techniques in particular are prone to internal defects inherently present due to the nature of the process, which have a detrimental effect on fatigue properties. In the present work, Ti6Al4V and Inconel 718 coupons with artificially induced defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…[189][190][191] Based on this consideration, the defect-based fracture mechanics methods have been successfully employed to predict the fatigue life of AM materials and achieved good results. 37,46,55,[191][192][193][194][195][196][197][198] Many fatigue crack propagation models have been adopted to predict the fatigue life of AM metals. A simply modified version of the Paris equation is as follows:…”
Section: Fracture Mechanics Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[189][190][191] Based on this consideration, the defect-based fracture mechanics methods have been successfully employed to predict the fatigue life of AM materials and achieved good results. 37,46,55,[191][192][193][194][195][196][197][198] Many fatigue crack propagation models have been adopted to predict the fatigue life of AM metals. A simply modified version of the Paris equation is as follows:…”
Section: Fracture Mechanics Methodsmentioning
confidence: 99%
“…There are many defects in AM metals, and the cracks usually initiate from the critical defects 189–191 . Based on this consideration, the defect‐based fracture mechanics methods have been successfully employed to predict the fatigue life of AM materials and achieved good results 37,46,55,191–198 …”
Section: Non‐ml‐based Methods For Fatigue Life Prediction Of Am Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser additive manufacturing technology (LAM) is becoming an increasingly popular manufacturing technology in aerospace industry. In LAM process, high-energy laser deposit metallic wires or powders, layer-by-layer, to build components [1][2][3][4]. The high-efficiency and fast-forming process does not require subsquent expensive tooling and machining, enabling the directly fabrication of near-net-shaped components.…”
Section: Introductionmentioning
confidence: 99%
“…During the fission neutron irradiation, or even at the fabrication stage, some point defects, such as vacancies and hydrogen (H) atoms, are generated in the material [ 17 , 18 , 19 , 20 , 21 ]. These point defects can further form clusters and lead to adverse mechanical degradation [ 22 , 23 , 24 ] or even change the phase of nuclear fuel [ 25 ]. It is found that voids or dislocation loops formed in α-U can lead to the hardening of the material [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%